2002
DOI: 10.1111/1540-6237.00114
|View full text |Cite
|
Sign up to set email alerts
|

Culture Wars in the Congressional Theater: How the U.S. House of Representatives Legislates Morality, 1993–1998

Abstract: Objective. This article explores the politics of cultural conflict in the U.S. House of Representatives (1993Representatives ( -1998 by analyzing legislator decision making on reproductive issues. Because reproductive policies represent a major contemporary cultural cleavage between feminists and religious traditionalists, decision making should be influenced by elite-and district-level variables reflective of culture. Methods. Prochoice support scores are derived and, using OLS, are regressed on elite-and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
(53 reference statements)
0
25
0
Order By: Relevance
“…While previous research on abortion found that legislator partisanship, religion, and ideology informed legislator decision making, we found that district‐level variables significantly shape decision making on gay issues. In a more systematic way than Oldmixon (2002) found in her abortion analyses, legislators appear to be synthesizing district‐level attitudes in their own decision‐making calculus. Legislators do not simply bow to the pressures of their constituents; nor do they act as brave trustees.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…While previous research on abortion found that legislator partisanship, religion, and ideology informed legislator decision making, we found that district‐level variables significantly shape decision making on gay issues. In a more systematic way than Oldmixon (2002) found in her abortion analyses, legislators appear to be synthesizing district‐level attitudes in their own decision‐making calculus. Legislators do not simply bow to the pressures of their constituents; nor do they act as brave trustees.…”
Section: Discussionmentioning
confidence: 93%
“…However, the national government is increasingly an arena of conflict on gay issues. Therefore, this research focuses on the U.S. House of Representatives, and it builds on previous cultural/morality policy research also conducted at this level (Adams 1997; Haider‐Markel 1999, 2001; Oldmixon 2002; Steiner 1983; Tatalovich and Schier 1993; Wattier and Tatalovich 1995).…”
Section: Culture Congress and Gay Issuesmentioning
confidence: 99%
“…Most of the support for the proposition emanates from studies of Congressional voting in the 1970s through the early 1990s that found women were generally more liberal than their male colleagues (Burrell 1994;Clark 1998;Frankovic 1977;Leader 1977;Vega and Firestone 1995;Welch 1985). In addition, other studies limited specifically to voting patterns on women's issues have found that gender is a significant indicator of taking the liberal position as well, especially as it applies to female Republicans (Burrell 1994;Dodson 2006;Dolan 1997;Evans 2005;Leader 1977;Oldmixon 2002;Swers 1998Swers , 2002Tatalovich and Schier 1993). 10 However, many scholars have failed to unearth any significant link between gender status and liberalism using Poole and Rosenthal's DW-NOMINATE scores as the dependent variable (McCarty, Poole, and Rosenthal 1997;Schwindt-Bayer and Corbetta 2004).…”
Section: Multivariate Analysis Of the Impact Of Gender On Roll-call Imentioning
confidence: 99%
“…For a contentious issue such as abortion funding with two identifiable sides, the attitudes of citizens toward abortion may well be remarkably structured and shaped by demographic characteristics. Thus, research on abortion issues shows that citizen forces are an important determinant in policymaking (Meier and McFarlane 1993;Mooney and Lee 1995;Norrander and Wilcox 1999;Oldmixon 2002).…”
Section: Morality Policy and Abortion Fundingmentioning
confidence: 99%
“…Early studies on abortion issues compared Canadian and U.S. abortion politics (Tatalovich 1997), compared state abortion policies (Meier and McFarlane 1993), and attempted to explain why people hold their opinions on abortion (Cohen and Barrilleaux 1993;Norrander and Wilcox 1999). Recent research has studied abortion issues within a morality policy and politics framework, including examining state-level policy responses to abortion (Mooney and Lee 1995), exploring the influence of national forces upon state-level abortion initiatives (Roh and Haider-Markel 2003), and analyzing the abortion voting behavior of legislators in the U.S. House of Representatives (Oldmixon 2002). 2 But perhaps not all issues clearly related to abortion should, or could, be classified simply as morality policy.…”
mentioning
confidence: 99%